Exploring mental health needs, coping and suitable service modalities for people affected by coronavirus disease 19 (Bangladesh Journal of Psychiatry, 2024)
There was a general gap on coronavirus disease (COVID) 19 related mental health concerns and coping data from the peak period of pandemic. With the aim of ensuring evidence informed service delivery, this study explored mental health needs, coping mechanisms and preferred service modalities of the front-line healthcare workers (FLHWs), COVID 19 patients and family members of both patients and FLHWs. Sixty-three participants were included in this cross-sectional study which was conducted at the period from July 2020 to December 2020.  The FLHWs and patients were recruited using purposive sampling from a COVID 19 dedicated hospital in Narayanganj while the family members were selected through the contact detailed shared by the FLHWs and the patients. Three mental health professionals conducted the interviews over the phone using a semi-structured qualitative interview guide. The findings of the study were presented in three broad categories, namely a) concerns around psychosocial health and wellbeing, b) coping with COVID 19 and its impacts and c) preferred modalities for psychosocial service delivery. The results showed that, low mood was most common (68.3%) followed by irritability and anger (65.1%) and concerns about the future (61.9%) among the participants. A very high number of participants (74%) reported an increase in religious activity and faith. As strategies to cope with the pandemic crisis, the participants most commonly reported engagement in entertainment (27%), taking care of relationships (21%) and engagement in spirituality (17%). The most preferred modality of service was self-help materials (49%; online videos, booklets, posters/leaflets) followed by webinars (12%) and online counselling (10%). However, to enable evidence informed service delivery during any severe pandemic such as COVID 19, the mental health needs of FLHWS and their family members must be addressed.Bang J Psychiatry 2023;37(2):38-45